DOI: 10.14264/uql.2016.212
|View full text |Cite
|
Sign up to set email alerts
|

Engineering yeast shikimate pathway towards production of aromatics: rational design of a chassis cell using systems and synthetic biology

Abstract: Aromatic building blocks are amongst the most important bulk feedstocks in the chemical industry. As these compounds are commonly derived from petrochemistry, obtaining them is becoming more and more a matter of costs and sustainability. Biochemistry gives rise to a wealth of compounds that can potentially replace current petroleum-based chemicals or be used for novel materials. The aromatic compounds para-aminobenzoic acid (pABA) and para-hydroxybenzoic acid (pHBA) and the aromatics derived compound cis,ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 194 publications
(289 reference statements)
1
6
0
Order By: Relevance
“…In addition to what has been described in Box 2 , two commonly applied targets beyond the shikimate pathway are overexpression of the transketolase and deletion of the glucose-6-phosphate dehydrogenase. The latter, once a popular knockout target in yeast ( ZWF1 ) is rarely applied anymore, a trend that is in accordance with our findings from in silico metabolic modeling (Averesch, 2016 ): we found that the knockout rarely benefits the yield (opposing to its original intention); especially in case of reducing pathways it negatively impacts redox cofactor availability (NADPH production from PPP). This is supported by our previous study on production of pHBA (described above) (Williams et al, 2015 ), where knock-down of ZWF1 had an adverse effect on the product titer.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In addition to what has been described in Box 2 , two commonly applied targets beyond the shikimate pathway are overexpression of the transketolase and deletion of the glucose-6-phosphate dehydrogenase. The latter, once a popular knockout target in yeast ( ZWF1 ) is rarely applied anymore, a trend that is in accordance with our findings from in silico metabolic modeling (Averesch, 2016 ): we found that the knockout rarely benefits the yield (opposing to its original intention); especially in case of reducing pathways it negatively impacts redox cofactor availability (NADPH production from PPP). This is supported by our previous study on production of pHBA (described above) (Williams et al, 2015 ), where knock-down of ZWF1 had an adverse effect on the product titer.…”
Section: Discussionsupporting
confidence: 88%
“…In combination with the usual feedback-resistant DHAP synthase (and chorismate mutase) respective titers in the range of 1.3 and 0.37 g/L could be reached (Kim et al, 2014 ; Romagnoli et al, 2015 ). It is noteworthy that in a study on production of pABA in S. cerevisiae [(Averesch et al, 2016 ), see above], in glucose batch cultures phenylethanol titers of almost 0.1 g/L were obtained, which exceeded the target product, even though the chorismate mutase ( ARO7 ) was knocked out (Averesch, 2016 ). This was attributed to a flux overflow that degraded chorismate into prephenate and phenylpyruvate (Winter et al, 2014 ).…”
Section: Results—strain Engineering Strategies For Production Of Arommentioning
confidence: 99%
See 3 more Smart Citations